The right to health in pharmaceutical patent disputes - Emmanuel Kolawole Oke (South Centre, 2022)
This paper examines how the courts in three developing countries (Kenya, South Africa, and India) have addressed the tension between patent rights on pharmaceutical products and the right to health. The paper begins by examining the nature of the relationship between patent rights and the right to health. It thereafter explores the justiciability of the right to health in Kenya, South Africa, and India. Furthermore, the paper provides an analysis of how the courts in these three developing countries have adjudicated some of the pharmaceutical patent cases involving tensions between the right to health and patent rights. The paper contends that by incorporating the right to health into the adjudication of patent disputes, courts in developing countries can play a crucial role in improving access to medicines at affordable prices.
Keywords: 300; Gesundheitsversorgung; Grundrecht; Arzneimittel; Patent; Patentrecht; Kenia; Südafrika; Indien